Eclampsia An Obstetric Disaster - P Pradhan (Journal of Nepal Medical Association, 2004)
Eclampsia has been graded as fatal and dreadful disease even before Christ and is the important cause of maternal and perinatal mortality in developed and developing countries. Severe morbidity associated with eclampsia include placental abruptio, cerebral haemorrhage, cortical blindness, renal failure, disseminated intravascular coagulopathy, pulmonary oedema, psychosis and growth retardation and preterm or both. Present management of eclampsia aims to stop the convulsions, its recurrences, control of blood pressure and correct fluid and electrolyte balance and delivery of the baby. There have been great controversies about the best anticonvulsants to use. The randomised trials comparing magnesium sulphate with diazepam or phenytoin showed greater efficacy of magnesium sulphate in the control and prevention of recurrence of fits. Perinatal mortality is also better with magnesium sulphate. Intramuscular injection is painful and local abscess formation at the site of injection is possible. Control of dose is better with intravenous route therefore preferred. Magnesium sulphate should be continued for 24 hours after the delivery or after the last fit. Antihypertensive drug therapy is now a routine practice in the management of pre-eclampsia and eclampsia. Methyl dopa, Lobetelol, Nefedipine are well tried in pregnancy and safe in pregnancy. However, hydralazine intravenous is good for quick and smooth control of blood pressure. Termination of pregnancy has been an important part of the management of eclampsia. Studies have shown that maternal outcomes seems better with caesarean delivery compared to vaginal delivery. The caesarean section rate is high at 26.3-80.4% in different studies. Recently maternal mortality and morbidity has been greatly improved even in developing countries by better control of fits by magnesium sulphate and caring them in intensive care unit.